Pengaruh Cadangan Kerugian Penurunan Nilai (CKPN) Dan Petumbuhan Volume Pembiayaan Serta Inflasi Terhadap Non Performing Financing Pada Bank Umum Syariah di Indonesia Periode 2012-2016 - Mega Diah Alnikmatus Sholikhah; Isna Yuningsih; Ibnu Abni Lahaya (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
The purpose of this research is to test and analyze the effect of allowance for  impairment losses and growth in financing volume as well as inflation against non performing financing. This research was conducted at sharia commercial banks in Indonesia which determined by purposive sampling method with the total of samples as much as 120 data period quarterly 2012-2016. Analytical method that been used is multiple linear regression. The results of this study indicate that (1) Allowance for impairment losses has influence significant on non performing financing, (2)  Growth in financing volume has influence significant on non performing financing,  (3) Inflation has no significant to non performing financing. These  findings  indicate  that  banks  can  affect  the  non performing financing by improving the quality of earning assets, especially financing by applying a good fund allocation policy and maximizing the growth of financing in productive business activities. Increase financing in consumer activities besides will tigger aggregate demand growth above the potential output, will also potentially become high-risk financing. As a result, banks will take more funds from capital to reserve the possibility of loss due to not return of the financing.Keyword :   Allowance for impairment losses, Growth in financing volume, Inflation, Non Performing Financing